2022
DOI: 10.1039/d2sm01113a
|View full text |Cite
|
Sign up to set email alerts
|

Collecting differently sized particles on water surface by maneuvering pedal waves on the foot of the water snail Pomacea canaliculata

Abstract: The water snail (Pomacea canaliculata) is featured in both broad dietary scope and high feeding rate, possibly making it one of the most successful mollusc invaders globally. The water snail...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several studies have shown that GST activity in the digestive glands of snails increased when exposed to pesticides or pollutants. Studies found that cadmium increased GST activity in the digestive glands of P. canaliculata [ 43 ]. This is consistent with our findings that the treatment increased GST, especially at 48 h, and that male snails had higher GST enzyme activity compared with females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that GST activity in the digestive glands of snails increased when exposed to pesticides or pollutants. Studies found that cadmium increased GST activity in the digestive glands of P. canaliculata [ 43 ]. This is consistent with our findings that the treatment increased GST, especially at 48 h, and that male snails had higher GST enzyme activity compared with females.…”
Section: Discussionmentioning
confidence: 99%
“…P. canaliculata has a feeding pattern that utilizes the surface of its feet to generate pedal waves that float across the air–water interface to collect food. Thus, dissolution of muscle fibers in the feet may cause disruption of feeding behavior [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 However, owing to its lack of flavour and high processing costs, this snail was discarded by farmers, resulting in its entry into natural aquatic environments. 9 Owing to its varied feeding habits, substantial dietary needs, swift reproductive rates, adaptability and the absence of natural predators, P. canaliculata has swiftly formed substantial populations in natural habitats, resulting in notable harm to local agricultural and wetland ecosystems. 10,11 Moreover, it serves as an intermediate host for parasites that pose human health risks, such as Angiostrongylus cantonensis and Echinostoma revolutum.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-air interfaces also act as a cradle to Neuston, organisms that inhabit at and below the water surface. For example, the underwater apple snail Pomacea canaliculata exploits the water surface to drive a large-scale surface flow and fetch floating food particles from afar in a process called pedal surface collection [24][25][26][27] . Whirligig beetles and water striders have developed morphological features to manipulate flow around them for effective locomotion at the interface 28,29 .…”
mentioning
confidence: 99%
“…Here, we reveal how a rhythmically deforming solid boundary pumps viscous liquid at the interface, and transports floating objects from distances much larger than its size. Our design, inspired in part by the capability of underwater snails in creating flow through undulations on their flexible foot 26,27 , produces traveling waves on an undulator. Even though traveling boundaries are a canonical strategy to drive flow within enclosed spaces when placed near a liquid-air interface, the undulator gives rise to non-intuitive observations; pumping does not increase proportionally to the wave speed, and we observe non-monotonicity in the average motion of surface floaters as the wave speed is gradually increased.…”
mentioning
confidence: 99%